2019
DOI: 10.33314/jnhrc.v16i41.1159
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Maternal and Fetal Outcome in Patients with Eclampsia

Abstract: Background: Eclampsia is a multisystem disorder that may lead to deterioration of maternal condition, hypoxia and acidosis of fetus. Objective was to evaluate the risk factors associated with adverse maternal and fetal outcome in patients with eclampsia. Methods: All patients with eclampsia were enrolled after informed consent from February 2013 to February 2014. Questions as per per-forma were asked to the patients and attendants about antenatal visits, parity, number of episodes of seizures, duration from on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…There were 3(13.63%) perinatal death and all were stillbirth cases. Similar finding was noted in study done by Jadav et al 18 where 15% of babies born were stillbirth and 11% in a study done by Pradhan et al 22 Most of the baby's i.e. 72.72% were delivered preterm and 59.09% were of low birth weight.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There were 3(13.63%) perinatal death and all were stillbirth cases. Similar finding was noted in study done by Jadav et al 18 where 15% of babies born were stillbirth and 11% in a study done by Pradhan et al 22 Most of the baby's i.e. 72.72% were delivered preterm and 59.09% were of low birth weight.…”
Section: Discussionsupporting
confidence: 87%
“…Similar finding was reported by Kamrun N et al16 where 40% patient received ICU care and 51.42% were treated in eclampsia ward. In a study done by Dalal et al,13 24.77% patient required ICU care and Pradhan et al22 reported that 31 patient out of 52 required ventilator support for respiration. These findings warrant urgent need of referral of all cases of eclampsia to tertiary care center.…”
mentioning
confidence: 98%
“…Tertiary level of education, eclampsia, gestational diabetes, delayed ANC initiation, number of ANC visits, being multiparous and home delivery were found to be signi cantly associated with adverse birth outcomes in this study. Eclampsia has been found to cause deterioration of maternal conditions which result into adverse foetal outcomes such as low birthweight and still births (37). In Ethiopia, adverse neonatal outcomes such as macrosomia, preterm births and large for gestational age was found to be signi cantly higher among newborns from mothers with gestational diabetes (38), which is similar to ndings in this study.…”
Section: Discussionsupporting
confidence: 86%
“…A systemic analysis showed that the incidence of eclampsia ranges from 0 to 0.1% in Europe, 4% in Nigeria, 0.6% in Brazil. Majority of the cases of eclampsia are seen in young 6 primigravidas and those with no prior antenatal care. 4,6 The case fatality rate of eclampsia is 1.8% in developed 7 countries, 17.7% in India and 13% in Nepal.…”
mentioning
confidence: 99%
“…Majority of the cases of eclampsia are seen in young 6 primigravidas and those with no prior antenatal care. 4,6 The case fatality rate of eclampsia is 1.8% in developed 7 countries, 17.7% in India and 13% in Nepal. The common causes of maternal deaths in eclampsia are coagulopathy, cerebrovascular haemorrhage, HELLP syndrome, Acute Renal Failure (ARF), aspira on pneumonia, pulmonary oedema, AntePartum Haemorrhage (APH), Postpartum haemorrhage (PPH) whereas perinatal mortality is due to preterm delivery, low birth weight, birth 2,8 asphyxia and intrauterine growth restric on.…”
mentioning
confidence: 99%